2008
DOI: 10.1111/j.1095-8649.2008.01749.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and genetic variations of satellite DNAs inAcrossocheilus paradoxus(Günther, 1868) (Cyprinidae) indicate population expansion

Abstract: A Hin dIII repetitive DNA family from Acrossocheilus paradoxus, a cyprinid fish endemic to Taiwan, was isolated and identified as a tandem arrangement of satellites in the genomic DNA. Cross-hybridization revealed similar patterns across fish genera and two families and suggested that this repetitive DNA is a conserved satellite sequence in fish. Forty-five monomeric repeat units of the repetitive DNA were cloned and sequenced, and found to be approximately 210 base pairs long and to have an average base compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…This is thought to occur either by genetic isolation between populations or by the propagation of new mutational variants across neighboring populations through molecular biological processes such as biased gene conversion (Elder & Turner, ). Similar results were recorded in A. paradoxus (Tseng et al., ) for the satellite sequence to which our Labeobarbus satellite matches. In agreement with this, we analyzed a set of Hin dIII satellite SNPs independently to our neutral SNPs and found similar results of genetic structure between the populations identified in this study (data not shown).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is thought to occur either by genetic isolation between populations or by the propagation of new mutational variants across neighboring populations through molecular biological processes such as biased gene conversion (Elder & Turner, ). Similar results were recorded in A. paradoxus (Tseng et al., ) for the satellite sequence to which our Labeobarbus satellite matches. In agreement with this, we analyzed a set of Hin dIII satellite SNPs independently to our neutral SNPs and found similar results of genetic structure between the populations identified in this study (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Cyprinid genomes include extensive repetitive regions (Henkel et al, 2012) such as the HindIII satellite (Datta, Dutta, & Mandal, 1988;Tseng, Chiang, & Wang, 2008), which is prevalent in our dataset at a frequency of 4.26% prior to filtering, with 7.47% of the loci in the final dataset potentially affiliated with this satellite. The prevalence of this satellite in our data exceeds that of all satellites across the C. carpio genome (2.46%) (Xu et al, 2011).…”
Section: Bioinformatics and Snp Discoverymentioning
confidence: 99%